Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/mpg.0000000000001413
|View full text |Cite
|
Sign up to set email alerts
|

NASPGHAN Capsule Endoscopy Clinical Report

Abstract: Wireless capsule endoscopy (CE) was introduced in 2000 as a less invasive method to visualize the distal small bowel in adults. Because this technology has advanced it has been adapted for use in pediatric gastroenterology. Several studies have described its clinical use, utility, and various training methods but pediatric literature regarding CE is limited. This clinical report developed by the Endoscopic and Procedures Committee of the North American Society of Pediatric Gastroenterology, Hepatology and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 107 publications
0
29
0
Order By: Relevance
“…One study reported that use of PC is a useful screening tool in adolescents, 31 but it is controversial whether younger children should undergo PC examination because they cannot swallow the PC and sedation solely for endoscopic deployment of PC is not recommended. 32 At the same time, several studies have shown that radiological SB imaging, such as barium SB follow through, computed tomographic enteroclysis and magnetic resonance enteroclysis does not exclude SB stenosis. 30 , 32 Our low capsule retention rate can be explained by careful patient selection with frequent use of PC in patients older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that use of PC is a useful screening tool in adolescents, 31 but it is controversial whether younger children should undergo PC examination because they cannot swallow the PC and sedation solely for endoscopic deployment of PC is not recommended. 32 At the same time, several studies have shown that radiological SB imaging, such as barium SB follow through, computed tomographic enteroclysis and magnetic resonance enteroclysis does not exclude SB stenosis. 30 , 32 Our low capsule retention rate can be explained by careful patient selection with frequent use of PC in patients older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“… 32 At the same time, several studies have shown that radiological SB imaging, such as barium SB follow through, computed tomographic enteroclysis and magnetic resonance enteroclysis does not exclude SB stenosis. 30 , 32 Our low capsule retention rate can be explained by careful patient selection with frequent use of PC in patients older than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for VCE in the pediatric population outlined in the ESPHGAN guidelines were followed. [ 3 ] VCE was used when a diagnosis could not be confirmed with gastroscopy or to supplement the diagnosis reached via colonoscopy. The groups were identified by their chief complaints and main clinical features.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[ 1 , 2 ] The United States Food and Drug Administration approved the use of CE for the evaluation of small bowel diseases in adults in 2001. In 2004, CE was approved for children 10 years or older; [ 3 ] Both CE and patency capsules were approved for use in children older than 2 years in 2009. [ 4 ] VCE is used for the diagnosis and assessment of the extent of disease in the small bowel, such as for Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to identify risk factors associated with CR. CR rate does not correlate with capsule size (13)(14)(15)(16)(17), and/or patient's age (18)(19)(20). Conversely, the rate strictly depends on clinical indication.…”
Section: Preventing Crmentioning
confidence: 97%